A hybrid high-gain bipolar converter for LVDC microgrid with average current mode control - Md Abdullah Al-Hysam; Dávid Raisz (Energy Conversion and Management: X)
The increasing demand for renewable energy accounts for the DC microgrid concept, facilitating the integration of photovoltaic (PV) modules and battery energy systems (BESS) into a common DC bus. In light of this, bipolar DC-DC converters can result in two symmetric DC buses that provide more flexibility. This article presents a hybrid bipolar converter by merging a single-ended primary-inductor converter (SEPIC) and a Cuk converter with a switched-inductor configuration in lieu of the input inductors for gain enhancement. The architecture holds the advantages of both the SEPIC and Cuk converters and has one active switch, resulting in a simple control circuitry. Incorporating the average current mode (ACM) control strategy, the proposed converter is capable of providing a bipolar output, each having a higher voltage gain than the conventional converters. A 510 W prototype, validated in a power hardware-in-the-loop (PHIL) laboratory environment, demonstrated a peak efficiency of 97.14 %, close to the theoretical projection of 99 %. The proposed topology contributes to advancing clean energy technologies by enabling efficient and reliable energy conversion for renewable-based microgrids.